The intensity of ground motion from future earthquakes in the Mentawai Islands, Sumatra - Han, Xiaohan. (2010)
From the clues of the historic rupture events on the Mentawai segment of the Sumatran Megathrust, the new rupture cycle has arrived signalled by the September 2007 earthquake events. The accumulated strain since last gigantic rupture in 1797 and 1833 is sufficient to generate an earthquake with Mw 8.8. The striking of the earthquake will cause physical damages to infrastructures, result in life losses and bring social and economical consequences. This report presents the procedures of seismogram synthesis for the hypothetical earthquake and dynamic analysis of structural responses. Evaluation of vulnerability of buildings was done by comparing the ductility demand imposed by the earthquake to the ductility capacity defined in the Indonesian seismic design code. The results include three parts. The first part presents the intensities of ground motion; the second part is the assessment of structural vulnerability; the last part provides the contour maps of peak ground accelerations and pseudo-acceleration of structures in Sumatra Island. The simulation result and response analysis showed that the rupture of the Mentawai segment of Sumatran megathrust will bring structural damages to the cities located in the central and west coast of Sumatra, such as Padang and Pekanbaru. Most medium to high rise buildings in Padang and Pekanbaru will yield. Buildings in other part of Sumatra are barely yielded depending on structural details. Tremors will be felt as far as Medan, Jakarta and Singapore. The ground shaking will not impose significant damage to structures in these cities.